Whom Do You Trust?: Investor-Advisor Relationships and Mutual Fund Flows - Kostovetsky, Leonard (Review of Financial Studies, 2016)
I provide a measure for the value that investors place on trust and relationships in asset management by examining mutual fund flows around announced changes in the ownership of fund management companies. I find a decline in flows of around 7% of fund assets in the year following the announcement date, resulting primarily from fund outflows. Retail investors and investors in funds with higher expense ratios are most responsive to ownership changes, providing evidence that such investors appear to place a significant value on trust and are more likely to respond to a relationship disruption by withdrawing their assets.